A review of the in-field transporting machines currently used in oil palm plantations in Malaysia - AlJawadi, Rafea Abdulsattar Mohammed; Mat Nawi, Nazmi; Wan Ismail, Wan Ishak; Ahmad, Desa; Mohd Kassim, Muhamad Saufi (University of Basrah, College of Agriculture, 2021)
This paper focuses on the in-field transporting machines currently used in oil palm plantations in Malaysia. It highlights the field conditions, the capacity of the machines and the time of completion of the transporting process which help to identify the determinants of the development of agricultural mechanization in Malaysian oil palm plantations. Understanding of the issues will help facilitate the elimination of weaknesses and defects prior to the manufacturing or modification stage. This will assist designers and manufacturers in the development and production of improved and more efficient field transportation equipment.